2022
DOI: 10.3389/fcell.2022.1040311
|View full text |Cite
|
Sign up to set email alerts
|

Functional and clinical characteristics of focal adhesion kinases in cancer progression

Abstract: Focal adhesion kinase (FAK) is a non-receptor tyrosine kinase and an adaptor protein that primarily regulates adhesion signaling and cell migration. FAK promotes cell survival in response to stress. Increasing evidence has shown that at the pathological level, FAK is highly expressed in multiple tumors in several systems (including lung, liver, gastric, and colorectal cancers) and correlates with tumor aggressiveness and patient prognosis. At the molecular level, FAK promotes tumor progression mainly by alteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 233 publications
1
4
0
Order By: Relevance
“…The focal adhesion kinase (FAK) is a tyrosine kinase that mediates the transduction of signals from integrin receptors to the downstream targets, such as PI3K/Akt and MAPKs [28]. FAK is activated by autophosphorylation at Y397 upon integrin binding to ECM proteins and to other ligands [28]. In the present study we found that dECM-triggered paracrine factor upregulation coincided with a decrease in the level of FAK phosphorylation at Y397.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The focal adhesion kinase (FAK) is a tyrosine kinase that mediates the transduction of signals from integrin receptors to the downstream targets, such as PI3K/Akt and MAPKs [28]. FAK is activated by autophosphorylation at Y397 upon integrin binding to ECM proteins and to other ligands [28]. In the present study we found that dECM-triggered paracrine factor upregulation coincided with a decrease in the level of FAK phosphorylation at Y397.…”
Section: Discussionsupporting
confidence: 50%
“…The focal adhesion kinase (FAK) is a tyrosine kinase that mediates the transduction of signals from integrin receptors to the downstream targets, such as PI3K/Akt and MAPKs [28]. FAK is activated by autophosphorylation at Y397 upon integrin binding to ECM proteins and to other ligands [28].…”
Section: Discussionmentioning
confidence: 99%
“…5A, B ; full results in Supplementary Data 2 and 3 ) revealed concordant results with these observations, showing significant enrichment in signatures related to cell adhesion and motility, fibronectin binding, as well as upregulation of VEGF signaling and HIF1 hypoxia signaling pathway. Upregulation of cell adhesion signaling pathway triggered by cell interaction with ECM was noted in responders including protein tyrosine kinase (PTK2) signaling, a member of focal adhesion kinase (FAK) subfamily (Supplementary Data 3 ; Reactome GSVA) 23 . Moreover, RTK signaling pathways including MET, EGFR, PDGF and ERBB2 were upregulated in TEC.…”
Section: Resultsmentioning
confidence: 99%
“…They generated three types of rat models of cardiac engineered tissues (polyacrylamide gels and neonatal CFs) differing in the degree of stiffness (from nearly 29 to 125 kPa) and they observed a direct relationship between rigidity and cell phenotypic change. As in a murine model in vivo , the angiotensin-II receptor inhibitor candesartan was demonstrated to reduce proliferation, migration, and oxidative stress in CFs, by specifically lowering the protein levels of phosphorylated focal adhesion kinase protein (FAK), a cytoplasmatic, non-receptor tyrosine kinase, found to be overexpressed also in many tumors ( Zhang et al, 2022b ). Downstream to FAK, phosphatidylinositol 3-kinase/protein kinase B (PI3K/Akt), ERK1/2, NOX2, and ROS are components of the signaling cascade.…”
Section: The Shortening Gap Between Preclinical Research and Clinical...mentioning
confidence: 99%